Asuhan Keperawatan pada Anak Demam Hipertermia dengan Terapi Tepid Water Sponge di RSUD Abdoel Wahab Sjahranie - Armayanti, Dewi; Abiyoga, Aries (Universitas Muhammadiyah Malang, 2025)
Background: Fever is an increase in body temperature > 37.5 C, which is the body's natural process of fighting infections that enter the body. One way to treat fever is non-pharmacological in the form of tepid water sponge therapy to reduce body temperature. Purpose: This study aimed to determine changes in temperature before and after tepid water sponge therapy. Method: The method used for children with hyperthermia started with assessment, diagnosis, intervention, implementation, and nursing evaluation. Results: This nursing care was conducted directly for three children. On An. Z before the tepid water sponge therapy was performed at 38 C, An. Before the treatment, tepid water sponge therapy was conducted at 38.9 C and An. Y, before the tepid water sponge therapy was performed at 37.7 C. Then, the tepid water sponge therapy was given for three days with 15 minutes of administration, and a decrease in body temperature occurred in An. Z's body temperature becomes 37 C, An. M's body temperature becomes 36.9 C, and An. Y's body temperature became 36.6 C. Based on these results, giving tepid water sponge therapy reduced body temperature in children. Conclusion: This indicates that the application of tepid water sponge therapy for three days given to 3 children affected reducing body temperature because when a compress was applied, the temperature control center received that the body temperature was in a warm condition, so the high body temperature would immediately decrease